Diet and physical activity of primary school aged children and their association with child's overweight and obesity - Laitinen, Rebekka (My University, 2021)
Abstract Background: Overweight and obesity are common problems in children. it is significantly affected by lifestyles such as nutrition and physical activity. parental obesity as well as activity and family socioeconomic status also affect a child’s body mass index. Objectives: We examined whether the nutrition and physical activity of overweight and obese primary school-age Finnish children differ from those of normal weight. We also investigated relationship between nutrition and physical activity and fat percentage as well as interrelationship between nutrition and physical activity. Methods: Nutrition and food intake was studied using 5-day food diaries. Physical activity and background factors were determined using questionnaires completed at home. Children's height, weight, and body composition were measured during the study visit. Results: Overweight/obese children consumed more preserved vegetables, meat, seafood and fish products, coffee, juices and processed foods, spices and spicy sauces and salty snacks compared to normal weight children. There was a correlation between a child’s fat percentage and the use of meat, fats, “other foods” and beverages. Normal weight children were more active than overweight/obese. There was a significant difference between activity groups in nutrients in the PUFA-SFA ratio, retinol equivalent, and in “other grains”, beef and sausage. The fat percentage decreases the more active the child is. Conclusions: Children’s food intake and physical activity are related to each other and have an effect on child’s fat percentage and Body Mass Index. The consideration of body fat percentage in this study brings new and more detailed information about the factors influencing childhood obesity. Keywords: Children, Nutrition, Exercise, Physical activity, Overweight, Obesity, Fat percentage